(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper discusses the work towards the use of Sanskrit as best language for computer programming.Sanskrit as an object-oriented programming language could be a fascinating concept, albeit with significant challenges. Object-oriented programming (OOP) relies heavily on principles like encapsulation, inheritance, polymorphism, and abstraction to organize and structure code. Sanskrit, on the other hand, is a classical language primarily used for religious, philosophical, and literary purposes, with a structure quite different from modern programming languages. This paper explore how Sanskrit could be adapted for object-oriented programming. We want to use Sanskrit as computer language because the Sanskrit most ancient, unambiguous language. This idea using Sanskrit as computer language can connect the ancient history of language and modern application of a most effecting language. Grammar structure of Sanskrit language promote Sanskrit to be used as an object-oriented programming language.